The added value of an electronic monitoring and alerting system in the management of medication-overuse headache: A controlled multicentre study. (October 2017) - Tassorelli, Cristina; Jensen, Rigmor; Allena, Marta; De Icco, Roberto; Katsarava, Zaza; Miguel Lainez, J; Leston, Jorge A; Fadic, Ricardo; Spadafora, Santiago; Pagani, Marco; Nappi, Giuseppe; ,
Background: Medication-overuse headache (MOH) is a chronic disabling condition associated with a high rate of relapse. Methods: We evaluated whether the adoption of electronic-assisted monitoring, advice and communication would improve the outcome over a follow-up of 6 months in a controlled, multicentre, multinational study conducted in six headache centres located in Europe and Latin America. A total of 663 MOH subjects were enrolled and divided into two groups: the Comoestas group was monitored with an electronic diary associated with an alert system and a facilitated communication option, and the Classic group with a paper headache diary. Results: We observed a significantly higher percentage of overuse-free subjects in the Comoestas group compared with the Classic group: 73.1 vs 64.1% (odds ratio 1.45, 95% confidence interval 1.07–2.09, p  = 0.046). The Comoestas group performed better also regarding the number of days/month with intake of acute drugs and the level of disability [Migraine Disability Assessment Score: Comoestas group – 42.5 ± 53.6 (35.5–49.3) and Classic group – 27.5 ± 56.1 (20.6–34.3) ( p  < 0.003)]. Conclusion: The adoption of the electronic tool improved the outcome of patients suffering from MOH after withdrawal from overused drugs. Information and communication technology represents a valid aid for optimizing the management of chronic conditions at risk of worsening or of relapsing. Trial registration: The trial was registered at ClinicalTrials.gov (no. NCT02435056).